(untitled) (Archives of Mechanics - Test, 2010)
A model of two semi-infinite half-spaces of different thermoelastic solids is considered in welded contact under hydrostatic initial stress. The appropriate boundary conditions are satisfied at the interface to obtain the reflection and refraction coefficients of various reflected and refracted waves during incidence of the quasi-thermal wave. A particular numerical example is considered to show the effect of hydrostatic initial stress on these coefficients for a certain range of the angle of incidence.